Biosafety Aspects of Hybridoma Technology: Nature of Risks and Approaches to Their Management - Kateryna Shevchuk; Anastasia Baranovska; Andrii Chernetskyi; Nataliia Shchotkina; Alexander Besarab (Innovative Biosystems and Bioengineering)
This study investigates the biosafety aspects of hybridoma technology, focusing on the identification and management of associated risks. Monoclonal antibodies, essential tools in immunology, biotechnology, and medicine, are primarily produced through hybridoma technology. This process involves fusing B lymphocytes from immunized animals with myeloma cells to create hybridomas, which are then cultured to produce specific antibodies. The research highlights significant contamination risks, particularly from rodent-borne viruses and other pathogens, during both in vivo and in vitro cultivation. It systematically analyzes existing strategies for identifying and mitigating these risks at various stages of monoclonal antibody production, including hybridoma identification, cell fusion, and antibody purification. The study underscores the importance of stringent biosafety protocols and optimized purification methodologies to ensure the production of high-quality, contaminant-free monoclonal antibodies. Additionally, it emphasizes the necessity of comprehensive risk assessments and the implementation of advanced contamination control systems in laboratories. The conclusions drawn from this study provide valuable insights into enhancing the safety and efficacy of monoclonal antibody production. By addressing these biosafety concerns, the research supports the widespread application of monoclonal antibodies in scientific and medical fields, ensuring their reliability and effectiveness in various diagnostic and therapeutic contexts.